Efetividade do laser de baixa intensidade e toxina botulínica tipo A em pacientes com dor miofacial - Carli, Bethânia Molin Giaretta de (2013)
This study evaluated the effect of low intensity laser and botulinum toxin type A in the mouth opening and pain symptoms in patients with facial myalgia testing the hypothesis that low-intensity laser produces immediate effect, while botulinum toxin type A, more late. Sixteen patients from the Faculty of Dentistry, University of Passo Fundo signed a consent form but only fifteen completed the work that had randomized clinical delineation. The patients were divided into two groups: Group Laser patients received low intensity laser with GaAlAs, 100 mW, 830 nm wavelength in continuous light emission. 80 J/cm2 was applied masseter and temporalis muscles, three times a week at 48 hour intervals for two weeks excluding weekends; Group Toxin patients received 30 U of botulinum toxin type A in the same muscles in the first session and 15 U after fifteen days in the same locations. The evaluations were performed by the measurement of pain using the VAS scale and mouth opening using a digital caliper always before each application, during 30 days after the first session. Data were statistically analyzed with Student's t test with significance level of 5%. Thus it can be concluded that there was no statistically significant difference between the groups in terms of mouth opening and pain relief, but both groups were statistically effective in relieving pain but not as mouth opening